Alzheimer’s Disease Diagnosis by Detecting Exogenous Fluorescent Signal of Ligand Bound to Beta Amyloid in the Lens of Human Eye: An Exploratory Study - Kerbage, Charles; Sadowsky, Carl; Jennings, Danna; Cagle, Gerald; Hartung, Paul (Frontiers in Neurology, 2013)
We report results of a clinical exploratory human trial involving 10 participants using a combination of a fluorescent ligand and a laser scanning device, SAPPHIRE System, as an aid in the diagnosis of Probable Alzheimer’s disease (AD). To the best of our knowledge, this is the first time that such a technique has been used in vivo of a human lens. The primary goal of the clinical trial, in addition to safety assessment, was to evaluate efficacy of the system. By detecting specific fluorescent signature of ligand bound beta amyloid in the supranucleus region of the human lens, a two-fold differentiation factor between AD patients and Control groups is achieved. Data from our studies indicates that deeper regions of the supranucleus provide the highest measures of ligand bound fluorescence signal from both controls and AD patients. Further studies are underway involving a larger population for statistical evaluation of the method.